Practical Considerations for the Management of Cushing's Disease and COVID-19: A Case Report - Beretta, Federica; Dassie, Francesca; Parolin, Matteo; Boscari, Federico; Barbot, Mattia; Busetto, Luca; Mioni, Roberto; De Carlo, Eugenio; Scaroni, Carla; Fallo, Francesco; Vettor, Roberto; Maffei, Pietro (Frontiers in Endocrinology, 2020)
Introduction: Italy, since the end of February 2020, is experiencing the corona virus disease 2019 (COVID-19) pandemic that may present as an acute respiratory infection. We report on COVID-19 pneumonia in the context of a complex case of Cushing's disease (CD). Case Report: A 67-year-old man with CD, who was admitted to our hospital, presented with signs and symptoms of adrenal insufficiency with persistent hypotension and glycemia toward the lower limits. We progressively withdrew almost all treatments for diabetes and CD (pasireotide and metyrapone), and i.v. hydrocortisone was necessary. A tendency to hyperkalemia was probably associated to enoxaparin. We summarized the many possible interactions between medications of Cushing's syndrome (CS) and COVID-19. Conclusion: Adrenal insufficiency might be a clinical challenge that needs a prompt treatment also in CS patients during COVID-19 infection. We should consider the possibility to titrate or temporary halt medical therapies of CS in the context of COVID-19 infection. Unexpected hyperkalemia in CS patients under treatment with heparin might be the signal of aldosterone suppression.